The Role of Artificial Intelligence in Shaping the Future of Education: Opportunities and Challenges - Ivanashko, Oksana; Kozak, Alla; Knysh, Tetiana; Honchar, Katryna (My University, 2024)
Artificial intelligence has become a booming technology whereas it brings numerous positive changes within the educational process. The aim of the research is to describe the role of artificial intelligence in education through the analysis of its opportunities and challenges. The study involved the integration of qualitative (interviews, focus groups, and classroom observations) and quantitative methods (survey and statistical analysis). All the research procedures were organized according to the ethical standards for data collection and analysis. Over 50 recent scientific works were selected to analyze the research problem from different perspectives and present its comprehensive overview. The study involved 56 participants representing instructors from different institutions of higher education in Ukraine. The inclusion criteria were based on subject specialization, institution type, curriculum accreditation, and experience with artificial intelligence technologies. It was found that the positive impacts of artificial intelligence include personalized and adaptive learning, automated administrative tasks, enhanced support, e-learning facilitation, inclusivity, data-driven decision making, gamification, increased engagement, behaviour and predictive analytics, improved assessment. The challenges concerned the data privacy, security, bias, lack of understanding, transparency, necessity for additional training. The findings showed that the implementation of artificial intelligence through personalized learning, predictive analytics, intelligent tutoring systems, content creation systems, Virtual Reality, automated administrative tasks, and chatbots can shape the educational process effectively in future and modernize the future specialists’ training. The research results can be used within the educational institutions to increase the awareness of using artificial intelligence tools.
Keywords: artificial intelligence tools; automation; intelligent tutoring systems; personalized learning; Virtual Reality